La vacunación en la infancia (2004)
¿Qué es una vacuna?/Tuberculosis/Difteria/La tosferina/el tétanos/Poliomielitis/Hepatitis A/Hepatitis B/La varicela/Fiebre amarilla/Infecciones por neumococo/Infecciones por hemofilias influenza/Infecciones por meningococo/Influenza/Rubeola-sarampión-paperas/Consideraciones generales.